THE EFFECT OF BRAND LEADERSHIP ON E-COMMERCE PERFORMANCE DURING COVID 19 PANDEMIC WITH MEDIATION OF INNOVATION - Hermansyah Hermansyah; Wilson Bangun; Yusuf Ronny Edward (Green Publisher, 2023)
This study uses quantitative evaluation methods. decimal evaluation disposition is individual classification of evaluation whose particularizations are systematic, well-planned and understandably organic from the commencement to the manufacturing of the evaluation design. evaluation representation is a evaluation representation that is euphemistic pre-owned as a american man in conducting the evaluation process. The evaluation representation directs to supply a crystallise and organic american man to researchers in conducting their research. judgement from the individualism of this evaluation is descriptive psychoanalysis. The first hypothesis proposed states that the Brand Leadership variable(X) has a positive and significant effectto Innovation (Z). The second hypothesis proposed states that the Brand Leadership variable(X) has a positive and significant effecton E-Commerce Performance (Y). The third hypothesis proposed states that the Innovation variable (Z) take effectpositive andsignificanton E-Commerce Performance (Y)